1997
DOI: 10.1074/jbc.272.50.31576
|View full text |Cite
|
Sign up to set email alerts
|

G Protein β1γ2 Subunits Promote Microtubule Assembly

Abstract: ␣ and ␤␥ subunits of G proteins are thought to transduce signals from cell surface receptors to intracellular effector molecules. G ␣ and G ␤␥ have also been implicated in cell growth and differentiation, perhaps due to their association with cytoskeletal components. In this report G ␤␥ is shown to modulate the cytoskeleton by regulation of microtubule assembly. Specificity among ␤␥ species exists, as ␤1␥2 stimulates microtubule assembly, and ␤1␥1 is without any effect. Furthermore, a mutant ␤1␥2, ␤1␥2(C68S), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
85
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 44 publications
12
85
0
Order By: Relevance
“…Furthermore, whereas G proteins are normally associated with second messenger-generating enzymes, or ion channels, results from several laboratories suggest that G proteins may be involved in cell growth and differentiation, perhaps through their association with cytoskeletal components (21)(22)(23)(24)(25)(26). For example, an association of G␣ and G␤␥ with the microtubule cytoskeleton has been reported (21, 24 -26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, whereas G proteins are normally associated with second messenger-generating enzymes, or ion channels, results from several laboratories suggest that G proteins may be involved in cell growth and differentiation, perhaps through their association with cytoskeletal components (21)(22)(23)(24)(25)(26). For example, an association of G␣ and G␤␥ with the microtubule cytoskeleton has been reported (21, 24 -26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activating G␣, the association between G␣ and tubulin induces a GTPase activity in tubulin similar to that seen after the self-association of tubulin dimers during the formation of a microtubule (32). Recent studies have also shown that G␤ 1 ␥ 2 binds to microtubules and promotes microtubule assembly in vitro (26). These studies indicate that G proteins may modulate microtubule polymerization dynamics and cytoskeletal organization or function.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Each of these scenarios are also of note relative to the role of AGS3 (PINS)-G␣ i / G␣ o complexes in neuroblast processing in D. melanogaster and the defect in orientation of the mitotic spindle observed in the absence of PINS (9,10). In the latter situation, interaction of AGS3 (PINS) with G␣ i(GDP) /G␣ o(GDP) could "release" G␤␥ for effector regulation, which may involve the apparent localization of G␤␥ to microtubules and/or mitotic spindles (24,25). The detailed analysis of the interaction of AGS3 with G␣ presented in this report should greatly facilitate efforts to further FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their interaction with transmembrane receptors and lipid modification, G proteins are usually associated with the plasma membrane. Recently, increasing evidence has emerged that G proteins are also present at intracellular areas such as Golgi apparatus, endoplasmic reticulum, cytoskeleton, and even the nucleus (1)(2)(3)(4)(5). Moreover, some studies have also shown that activated G␣s can be released from the plasma membrane to the cytoplasm (6 -9).…”
mentioning
confidence: 99%